In The Production of A Language Culture, The Existence of Literature Works; Hindu-Buddhist Education in the Kingdom of Kediri - Nofradatu, Ali Salsabilla (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this paper is to discuss the presence of literary works in the kingdom of Kediri, the role of ancient Javanese language in Hindu-Buddhist education, and the relationship between the presence of literary works and the role of ancient Javanese language in Hindu-Buddhist education in order to produce language culture. This study employs the historical method and is based on the findings. Literary works are concrete images that create charm with language tools that communicate the human person's experiences, thoughts, feelings, ideas, passions, and beliefs in the shape of experiences, thoughts, feelings, ideas, passions, and beliefs. The existence of literary works in producing linguistic culture in Hindu-Buddhist education.